2023
DOI: 10.2196/40725
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Asynchronous Tool to Facilitate Communication Between Primary Care Providers and Cancer Specialists: Pragmatic Randomized Controlled Trial

Abstract: Background Cancer poses a significant global health burden. With advances in screening and treatment, there are now a growing number of cancer survivors with complex needs, requiring the involvement of multiple health care providers. Previous studies have identified problems related to communication and care coordination between primary care providers (PCPs) and cancer specialists. Objective This study aimed to examine whether a web- and text-based asyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Healthcare providers reported that PCPs were more likely to contact cancer specialists by telephone or fax after the patient completed treatment, in instances where a patient had more complex needs, or if the patient lived far away from the cancer center [ 18 ]. Results from the pRCT demonstrated that patients randomized to the intervention group had an average of three comorbid conditions in the treatment phase, and an average of two comorbid conditions in the survivorship phase [ 17 ], so there may have been less of a need for communication regarding patients who did not have as many illnesses.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Healthcare providers reported that PCPs were more likely to contact cancer specialists by telephone or fax after the patient completed treatment, in instances where a patient had more complex needs, or if the patient lived far away from the cancer center [ 18 ]. Results from the pRCT demonstrated that patients randomized to the intervention group had an average of three comorbid conditions in the treatment phase, and an average of two comorbid conditions in the survivorship phase [ 17 ], so there may have been less of a need for communication regarding patients who did not have as many illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…During this study, PCPs were still able to communicate with cancer specialists via usual channels while the eOncoNote intervention was active. We abstracted hospital EMR data on PCP and cancer specialist communication via the usual channels, which indicated that there were few calls made by PCPs or faxes sent to the cancer center during the treatment and survivorship phases [ 17 ]. Taken together, these results indicate that PCPs were not communicating with cancer specialists via usual channels instead of using eOncoNote, rather there was limited communication beyond the faxed consult notes from the specialist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations